2006
DOI: 10.1385/jmn:28:2:161
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein Budding Yeast Model: Toxicity Enhanced by Impaired Proteasome and Oxidative Stress

Abstract: Parkinson's disease (PD) is a common neurodegenerative disorder that results from the selective loss of midbrain dopaminergic neurons. Misfolding and aggregation of the protein alpha-synuclein, oxidative damage, and proteasomal impairment are all hypotheses for the molecular cause of this selective neurotoxicity. Here, we describe a Saccharomyces cerevisiae model to evaluate the misfolding, aggregation, and toxicity-inducing ability of wild-type alpha-synuclein and three mutants (A30P, A53T, and A30P/A53T), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 83 publications
5
57
3
1
Order By: Relevance
“…By varying the copy number and integration loci of -syn, we found an unusually strong dose dependence between -syn expression levels and toxicity (Cooper et al, 2006;Gitler et al, 2008); this is highly reminiscent of the extreme dosage sensitivity of -syn observed with certain dominantly inherited forms of PD (Singleton et al, 2003;Ibanez et al, 2009). In this model, -syn toxicity causes lipid droplet accumulation (Outeiro and Lindquist, 2003), impairs proteasome-mediated protein degradation (Chen et al, 2005;Sharma et al, 2006) and elicits vesicle trafficking defects (Outeiro and Lindquist, 2003;Soper et al, 2008) with specific ERto-Golgi blockade (Cooper et al, 2006;Gitler et al, 2008). All of these phenotypes have been observed in neuronal models and implicated in the pathogenesis of PD.…”
Section: Research Articlementioning
confidence: 99%
“…By varying the copy number and integration loci of -syn, we found an unusually strong dose dependence between -syn expression levels and toxicity (Cooper et al, 2006;Gitler et al, 2008); this is highly reminiscent of the extreme dosage sensitivity of -syn observed with certain dominantly inherited forms of PD (Singleton et al, 2003;Ibanez et al, 2009). In this model, -syn toxicity causes lipid droplet accumulation (Outeiro and Lindquist, 2003), impairs proteasome-mediated protein degradation (Chen et al, 2005;Sharma et al, 2006) and elicits vesicle trafficking defects (Outeiro and Lindquist, 2003;Soper et al, 2008) with specific ERto-Golgi blockade (Cooper et al, 2006;Gitler et al, 2008). All of these phenotypes have been observed in neuronal models and implicated in the pathogenesis of PD.…”
Section: Research Articlementioning
confidence: 99%
“…37,46 However, later reports showed that a-syn toxicity is dependent on the genetic background as in certain yeast strains the cells can be loaded with a-syn inclusions without showing a significant growth defect. 38,47 Moreover, cells of the fission yeast Saccharomyces pombe show extensive a-syn inclusion formation without any toxicity. 48 As WT-syn and the A53T mutant do not target the plasma membrane in S. pombe cells and, as such, behave in a manner similar to the A30P mutant in S. cerevisiae cells, it was hypothesized that the a-syn-derived toxicity would correlate better with the membrane binding capacity rather than with the fibrillization rate of the protein.…”
Section: 36mentioning
confidence: 99%
“…In fact, (over)expression of genes encoding key proteins involved in human dementias proved to be lethal to yeast cells, such as that for synuclein (depending on the genetic background of the yeast strain) and the protein TDP-43 involved in amyotrophic lateral sclerosis (ALS) [86,87]. In contrast, human tau overexpression from the GAL1/10 promoter in yeast, which lacks an endogenous tau homolog, does not produce any detectable phenotype in logarithmically growing wild-type cells [23,66].…”
Section: Tau Expression In Saccharomyces Cerevisiae and Merits Of Klumentioning
confidence: 99%
“…2 have been successfully expressed, and in many cases shown to functionally complement the respective yeast deletion mutants provided by either of the deletion collections kept in Stanford/USA or the EUROSCARF collection in Frankfurt/Germany. However, it should be noted that caution as to the genetic background of the yeast strain applied for specific purposes may be required, as examplified for the variations in toxic effects of synuclein gene expression [87].…”
Section: Genetic Screens In Yeast -The Past the Present And The Futurementioning
confidence: 99%